2018
DOI: 10.1002/jbm.a.36404
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the anti‐quorum sensing activity of a d‐limonene nanoemulsion for Escherichia coli O157:H7

Abstract: In this study, a d-limonene nanoemulsion was developed by using a spontaneous emulsification method and its potential to inhibit the quorum sensing (QS)-regulated properties of Escherichia coli O157:H7 (E. coli) were revealed. The results in this study showed that d-limonene nanoemulsion inhibited E. coli biofilm formation through the suppression of curli and extracellular polymeric substance (EPS) production without inhibiting cell growth, and decreased swimming and swarming ability. Further analyses showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Moreover, its long-term stability is also enhanced (Figure 5). In a recent work D-limonene was used to prevent the formation of biofilms on E.coli O157:H7 at sub-lethal doses, by blocking the quorum sensing mediated autoinducer-2 (AI-2) communication and curli-related gene expression (Wang et al, 2018).…”
Section: Micelles Liposomes and Nano-emulsionsmentioning
confidence: 99%
“…Moreover, its long-term stability is also enhanced (Figure 5). In a recent work D-limonene was used to prevent the formation of biofilms on E.coli O157:H7 at sub-lethal doses, by blocking the quorum sensing mediated autoinducer-2 (AI-2) communication and curli-related gene expression (Wang et al, 2018).…”
Section: Micelles Liposomes and Nano-emulsionsmentioning
confidence: 99%
“…Hereby, both swimming and swarming motilities were repressed. [24] The biosynthesis of the AI-2 signal is carriedo ut through cleavage of S-ribosylhomocysteine by LuxS ( Figure 1). [25] For signal detection, AI-2 is phosphorylated and derepresses transcription of target genes through binding to LsrR.…”
Section: Inhibition Of Ai-2 Signalingmentioning
confidence: 99%
“…[78] Also, b-lactam antibiotics as inhibitors of cell-wall biosynthesis affect virulence and population behavior at concentrations below the MIC.F or example, the third-generation cephalosporin ceftazidime (22)i nhibited virulence of P. aeruginosa PAO1 and PAF97 and reduced swarming motilityb ya round8 0% at 0.9 and 3.7 mm,r espectively (Scheme 2). [80] The antibioticsc efotaxime (23), ciprofloxacin (24), chloramphenicol, and trimethoprim completely blocked swarming of the gram-negative pathogen Salmonella enterica (ser.T yphimurium) at subgrowth inhibitory concentrations of 3.5, 0.02, 6, and 3 mm,r espectively.I nc ontrast, amikacin, colistin, kanamycin,a nd tetracycline did not inhibit swarming of S. enterica (ser.T yphimurium). While cefotaxime (23), ciprofloxacin (24)a nd trimethoprim inhibited polar-chemoreceptora rray assembly of S. enterica (ser.T yphimurium) that is essential for swarming, chloramphenicol inhibited swarming by ad ecrease in flagellation (Scheme 2).…”
Section: Sub-inhibitory Concentrations Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation is due to bacterium-bacterium interactions, and associations with higher organisms through intercellular communication, known as quorum sensing (QS) systems [70]. It has been suggested that D-limonene NEs inhibit QS-based virulence phenotypes in E. coli, including biofilm formation, curli and exopolysaccharides production, and swimming and swarming motility [70,71]. From the obtained results it can be hypothesized that SEO alone and, to a greater extent, SEO NEs, exerted an inhibitory activity on strong biofilm producers through modulation of QS molecule production or release, preventing the achievement of the threshold concentration for biofilm development.…”
Section: Discussionmentioning
confidence: 99%